Spectroscopic analysis of DNA strands influenced by magnetic field / Seyedeh Maryam Banihashemian - Banihashemian, Seyedeh Maryam (2014)

(untitled)
In recent years, the number of research related to biological sensing devices has increased tremendously. Investigations related to environmental effects on DNA involve multidisciplinary studies and are actively pursued due to its novelty. Studies on the behavior of some optical parameters of DNA under the influence of external magnetic field are therefore very interesting as it can lead to important applications in the biomedical field and electronics. These studies have been made possible with the availability and practicability of many highend optical measurement systems, which are currently available. In this work, spectroscopic characterizations on diluted DNA under external magnetic field were measured using ultra-violet-visible (UV-Vis) transmission and Raman scattering spectroscopy techniques. The absorption intensity, extinction coefficient and purity of double strands (extracted from Mimosa pudica) and oligonucleotide DNA were measured to study the biological related properties with respect to the magnetic field strength applied. The Physics aspects of the optical properties of the DNA such as band gap, refractive index and loss function of DNA were investigated as a function of various magnetic field strengths. Results indicate that there is an increase in the extinction coefficient for dsDNA with increase in the magnetic field strength due to breakage and cleavage of DNA strands. Thermal and resistance characterization were also studied on the effects of DNA exposure to magnetic field. The results show that exposure to the external magnetic field has some influence on the resistivity, optical parameters, temperature and hydrogen bond of the DNA ix strands. The large band gap of the DNA under study only shows a small change when exposed to magnetic fields stronger than 750 mT. This research concluded that the properties studied in relation to DNA exposure to the magnetic field shows strong potential for applications in the biomedical field particularly as tools in diagnostic testing and bio-engineering research.